Survival and Growth of Yeast without Telomere Capping by Cdc13 in the Absence of Sgs1, Exo1, and Rad9 - Ngo, Hien-Ping (Public Library of Science, 2010)
Maintenance of telomere capping is absolutely essential to the survival of eukaryotic cells. Telomere capping proteins, such as Cdc13 and POT1, are essential for the viability of budding yeast and mammalian cells, respectively. Here we identify, for the first time, three genetic modifications that allow budding yeast cells to survive without telomere capping by Cdc13. We found that simultaneous inactivation of Sgs1, Exo1, and Rad9, three DNA damage response (DDR) proteins, is sufficient to allow cell division in the absence of Cdc13. Quantitative amplification of ssDNA (QAOS) was used to show that the RecQ helicase Sgs1 plays an important role in the resection of uncapped telomeres, especially in the absence of checkpoint protein Rad9. Strikingly, simultaneous deletion of SGS1 and the nuclease EXO1, further reduces resection at uncapped telomeres and together with deletion of RAD9 permits cell survival without CDC13. Pulsed-field gel electrophoresis studies show that cdc13-1 rad9Δ sgs1Δ exo1Δ strains can maintain linear chromosomes despite the absence of telomere capping by Cdc13. However, with continued passage, the telomeres of such strains eventually become short and are maintained by recombination-based mechanisms. Remarkably, cdc13Δ rad9Δ sgs1Δ exo1Δ strains, lacking any Cdc13 gene product, are viable and can grow indefinitely. Our work has uncovered a critical role for RecQ helicases in limiting the division of cells with uncapped telomeres, and this may provide one explanation for increased tumorigenesis in human diseases associated with mutations of RecQ helicases. Our results reveal the plasticity of the telomere cap and indicate that the essential role of telomere capping is to counteract specific aspects of the DDR.